Pengaruh Pengetahuan Mahasiswa Tentang Uji Kompetensi Terhadap Minat Belajar Mahasiswa D-III Kebidanan Di STIKes Prima Nusantara Bukittinggi Tahun 2013 - Nurkhasanah, Siti; Fitri Rahmadhaniaty, Fitri (Jurnal Kesehatan - STIKes Prima Nusantara, 2013)
In order to guarantee the quality of higher education graduates in particular areas of Midwifery and Nursing, it is necessary to standardize graduate memalui competency test. Indonesia requires qualified human resources for health, particularly midwives. The study aims to determine the effect of student knowledge about the competency test against midwifery students' learning interest in prime stikes bukittinggi archipelago, cross sectional research design, from February to August 2013, 186 people and the number of samples proportional sampling technique samples. The collection of data through documentation and anket number of midwifery students with questionnaires, the data were processed and analyzed by computer. The results showed that the students have a high knowledge of the competency test and also have a high interest in learning as much as 53 respondents (55.2%), students have the knowledge about testing and have a low interest in learning as much as 43 respondents (44.8%). Students have low knowledge about the competency test but has a high interest in learning as much as 38 respondents (42.8%) and students who have low knowledge and low interest in learning as much as 52 respondents (57.8%). Based on the variables studied did not have a significant relationship to the knowledge of students about the competency test on students' learning interest with p-value of 0.081. Thus students are expected to increase the knowledge about the development of midwifery accompanied with high motivation and interest to be able to graduate with the quality of quality.